Bespoke smoking cessation for people with severe mental ill health (SCIMITAR): a pilot randomised controlled trial. (May 2015) - Gilbody, Simon; Peckham, Emily; Man, Mei-See; Mitchell, Natasha; Li, Jinshuo; Becque, Taeko; Hewitt, Catherine; Knowles, Sarah; Bradshaw, Tim; Planner, Claire; Parrott, Steve; Michie, Susan; et al.
Summary: Background: People with severe mental ill health are three times more likely to smoke but typically do not access conventional smoking cessation services, contributing to widening health inequalities and reduced life expectancy. We aimed to pilot an intervention targeted at smokers with severe mental ill health and to test methods of recruitment, randomisation, and follow up before implementing a full trial. Methods: The Smoking Cessation Intervention for Severe Mental Ill Health Trial (SCIMITAR) is a pilot randomised controlled trial of a smoking cessation strategy designed specifically for people with severe mental ill health, to be delivered by mental health nurses and consisting of behavioural support and drugs, compared with a conventional smoking cessation service (ie, usual care). Adults (aged 18 years or older) with bipolar disorder or schizophrenia, who were current smokers, were recruited from NHS primary care and mental health settings in the UK (York, Scarborough, Hull, and Manchester). Eligible participants were randomly allocated to either usual care (control group) or usual care plus the bespoke smoking cessation strategy (intervention group). Randomisation was done via a central telephone system, with computer-generated random numbers. We could not mask participants, family doctors, and researchers to the treatment allocation. Our primary outcome was smoking status at 12 months, verified by carbon monoxide measurements or self-report. Only participants who provided an exhaled CO measurement or self-reported their smoking status at 12 months were included in the primary analysis. The trial is registered atISRCTN.com, number ISRCTN79497236. Findings: Of 97 people recruited to the pilot study, 51 were randomly allocated to the control group and 46 were assigned to the intervention group. Participants engaged well with the bespoke smoking cessation strategy, but no individuals assigned to usual care accessed NHS smoking cessation services. At 12 months, 35 (69%) controls and 33 (72%) people assigned to the intervention group provided a CO measurement or self-reported their smoking status. Smoking cessation was highest among individuals who received the bespoke intervention (12/33 [36%] vs 8/35 [23%]; adjusted odds ratio 2·9, 95% CI 0·8–10·5). Interpretation: We have shown the feasibility of recruiting and randomising people with severe mental ill health in a trial of this nature. The level of engagement with a bespoke smoking cessation strategy was higher than with a conventional approach. The effectiveness and safety of a smoking cessation programme designed particularly for people with severe mental ill health should be tested in a fully powered randomised controlled trial. Funding: National Institute of Health Research Health Technology Assessment Programme.